ANALISIS KELAYAKAN INVESTASI DANA HAJI UNTUK PEMBANGUNAN PROYEK INFRASTRUKTUR JALAN TOL JAKARTA - CIKAMPEK II ELEVATED (Politeknik Negeri Jakarta, 2021)
Increasing the welfare of the Indonesian people, especially Muslims, encourages them to carry out religious activities that require financial readiness, namely the pilgrimage. The enthusiasm of Indonesian Muslims to register for Hajj is not comparable to the available quota, which results in a longer waiting time for Hajj departures. The registrants for prospective pilgrims have increased every year. There are 3,797,376 applicants who wish to carry out the haj pilgrimage until June 2018, while the annual quota provided for Indonesia is only 210,000 people. As a result, there has been an increase in the deposition of funds for the initial deposit of prospective pilgrims in the Ministry of Religion's accounts, until March 2018 it has collected as much as IDR 105,191,372,936,614. This study aims to assess whether the hajj funds are worth investing in toll road infrastructure projects. Starting from problem identification to calculating investment feasibility to cooperation agreements in managing Hajj funds with Islamic banks with the Musyarakah Mutanaqishah agreement scheme. to finance toll road infrastructure projects. The capital budgeting method is used to calculate investment feasibility, so it can be seen that the NPV value is IDR 54,805,724,000,000 then the IRR value is 62%, BCR is 3.61, and the payback period is 12 years. With this assessment, it is worth investing in the hajj funds for the users of the Jakarta - Cikampek II Elevated toll road infrastructure project.